Analisis Putusan Nomor 145 K/Tun/2017 Berdasarkan Asas-Asas Umum Pemerintahan Yang Baik - Indah Herawati; Hanung Shafa; Jean Daniel (Jurnal Ilmiah Wahana Pendidikan, 2023)
Constitutionally, the Republic of Indonesia can be said to be designed as a welfare state. This can be seen in a series of articles in the 1945 Constitution, starting from Article 27, 28, 31, 33, and Article 34 of the 1945 Constitution, the welfare state is one type of legal state that is considered modern. The principles of good governance were born during the development of the welfare state. This study reveals the legal basis of the general principles of good governance of some regulations. The results showed that the general principles of good governance is currently regulated comprehensively in the legislation in Indonesia. These regulations include 1) Law No. 5 of 1986 on administrative justice amended by 2) law No. 9 of 2004 (Administrative Court Act 2004) 3) Law No. 28 of 1999 on the implementation of a clean and Free State KKN 4) Law No. 37 of 2008 on Ombudsman 5) law no. 5 of 2014 on the State Civil apparatus 6) law No. 25 of 2009 on Public Service 7) Law No. 23 of 1024 on Local Government and 8) law no. 30 of 2014 on Government Administration). As a modern country, the general principle of good governance is the spirit for the implementation of the administration of the Republic of Indonesia, especially in the context of clean implementation of governance based on expediency, justice, and legal certainty.